Gli spazi immaginati - Bruna, Consarelli (Firenze University Press, 2005)
This volume represents the third publication in the series devoted to the theme "Figures in space, politics and society", promoted by a specific interdisciplinary study group, and is the result of the study day held in Florence in December 2003. The objective here is to set up comparisons with the suggestions thrown up by historical and literary evidence pertinent to the numerous modes of imagining space with reference to the political and social spheres. A series of extracts from sources collateral to the classical political panorama highlights the fertility of the line of research and the efficacy of the interdisciplinary approach adopted.